Laser microdissection-based analysis of the Y sex chromosome of the Antarctic fish Chionodraco hamatus (Notothenioidei, Channichthyidae) - Cocca, Ennio; Petraccioli, Agnese; Morescalchi, Maria Alessandra; Odierna, Gaetano; Capriglione, Teresa (Comparative Cytogenetics, 2015)
Microdissection, DOP-PCR amplification and microcloning were used to study the large Y chromosome of Chionodraco hamatus, an Antarctic fish belonging to the Notothenioidei, the dominant component of the Southern Ocean fauna. The species has evolved a multiple sex chromosome system with digametic males showing an X1YX2 karyotype and females an X1X1X2X2 karyotype. Fluorescence in situ hybridization, performed with a painting probe made from microdissected Y chromosomes, allowed a deeper insight on the chromosomal rearrangement, which underpinned the fusion event that generated the Y. Then, we used a DNA library established by microdissection and microcloning of the whole Y chromosome of Ch. hamatus for searching sex-linked sequences. One clone provided preliminary information on the presence on the Y chromosome of the CHD1 gene homologue, which is sex-linked in birds but in no other vertebrates. Several clones from the Y-chromosome mini-library contained microsatellites and transposable elements, one of which mapped to the q arm putative fusion region of the Y chromosome. The findings confirm that interspersed repetitive sequences might have fostered chromosome rearrangements and the emergence of the Y chromosome in Ch. hamatus. Detection of the CHD1 gene in the Y sex-determining region could be a classical example of convergent evolution in action.